Synthesis and dynamic de-wetting properties of poly(arylene ether sulfone)-graft-poly(dimethyl siloxane). (6th December 2017) - Shen, Kunzhi; Hu, Heng; Wang, Jiandong; Liu, Guojun
Abstract: Many test liquids cleanly glide down crosslinked coatings bearing nanopools of a grafted liquid ingredient for dewetting enablement (NP-GLIDE coatings) at low substrate tilt angles. It was unclear if an engineering plastic with a high glass transition temperature Tg could replace a crosslinked coating matrix to support an NP-GLIDE coating. This paper reports the uniform grafting via click chemistry of liquid poly(dimethyl siloxane) (PDMS) onto poly(arylene ether sulfone) (PAES, T g  = 185 °C) to yield graft copolymers PAES- g -PDMS with low polydispersity indices. Hexadecane droplets (5 μL) cleanly glided down at sliding angles (SAs) of less than 3 ± 1° on all of the coatings prepared from PAES- g -PDMS with PDMS weight fractions of 3.4%, 19%, 30%, and 40%, respectively. Further, an oil-based ink readily contracted on them. The sliding angle of 15 μL droplets decreased from 47 ± 2° to 13 ± 1° as the PDMS weight fraction increased from 3.4% to 30%. Graphical abstract: Highlights: Conditions for the uniform granfting of PDMS onto PAES established. On PAES- g -PDMS films, water and many organic liquids cleanly and readily slided. Surface and internal segregation patterns of PAES- g -PDMS established. PDMS shown to render anti-smudge properties to an engineering plastic.